Lithuanian Economy: Lessons of the Last Years - Geralavičius, Vaidievutis (Ekonomika, 2000)
Development of Lithuanian economy is surveyed for the period 1995-1999 I half in the paper. The period, except 1999, was very successful and Lithuania was among leading Central and East European countries by most of the macroeconomic indicators. When compared data for Lithuania with that for Estonia and Latvia, one can see no difference in levels of development of these countries, thus there is no reason to claim that Estonia was included into the first group of the EU candidates because of its advancement in economic development.In the paper, the most attention is paid to development and structure of DGP, to analysis of infliation, monetary policy, balance of payment’ and functioning of banking system. The main conclusions appear at the end of the paper. Among them: if economy of the EU grows 2% annually while Lithuanian economy makes 5%, Lithuania may achieve EU average only in 37,9 years and in 23,8 years the level of Greece, the weakest economy in the EU. Deflation does not pose any real danger, however, balance of payment’ may become dangerously high. Banking system proved to be the strongest chaim of economy best prepared for Russian crisis.